Two Ports Laparoscopic Inguinal Hernia Repair in Children - Ibrahim, Medhat M. (Minim Invasive Surg, 2015)
Introduction. Several laparoscopic treatment techniques were designed for improving the outcome over the last decade. The various techniques differ in their approach to the inguinal internal ring, suturing and knotting techniques, number of ports used in the procedures, and mode of dissection of the hernia sac. Patients and Surgical Technique. 90 children were subjected to surgery and they undergone two-port laparoscopic repair of inguinal hernia in children. Technique feasibility in relation to other modalities of repair was the aim of this work. 90 children including 75 males and 15 females underwent surgery. Hernia in 55 cases was right-sided and in 15 left-sided. Two patients had recurrent hernia following open hernia repair. 70 (77.7%) cases were suffering unilateral hernia and 20 (22.2%) patients had bilateral hernia. Out of the 20 cases 5 cases were diagnosed by laparoscope (25%). The patients' median age was 18 months. The mean operative time for unilateral repairs was 15 to 20 minutes and bilateral was 21 to 30 minutes. There was no conversion. The complications were as follows: one case was recurrent right inguinal hernia and the second was stitch sinus. Discussion. The results confirm the safety and efficacy of two ports laparoscopic hernia repair in congenital inguinal hernia in relation to other modalities of treatment.